1981
DOI: 10.3109/00016488109138511
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Methods for Measuring Nasal Mucociliary Clearance in Man

Abstract: Abstracf. Three techniques for studying nasal mucociliary clearance have been compared in 20 normal subjects, aged 19 to 26. Three different tracers used were deposited on Acta Otolatyngol9l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
8

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 9 publications
5
58
0
8
Order By: Relevance
“…Nasal mucociliary transit time (NMTT) assessment has been done using different materials including radioactive markers, insoluble charcoal and micro alluminum discs. In a study comparing three of the common methods, Puchelle et al [5], validated the suitability of using saccharin as a simple screening test for nasal mucociliary clearance times. As a consequence, commercially available medical grade saccharin sweetener was used which is both easily available and inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal mucociliary transit time (NMTT) assessment has been done using different materials including radioactive markers, insoluble charcoal and micro alluminum discs. In a study comparing three of the common methods, Puchelle et al [5], validated the suitability of using saccharin as a simple screening test for nasal mucociliary clearance times. As a consequence, commercially available medical grade saccharin sweetener was used which is both easily available and inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…In the statistics reviewed, [1][2][3][5][6][7][8][9][10] we found that the sample sizes varied from a minimum of 20 to a maximum of 50. Hence, we (based on feasibility) studied a total of 32 subjects in each of the groups (chronic rhinosinusitis, smokers, and controls); a total of 96 subjects were studied.…”
Section: Methodsmentioning
confidence: 99%
“…MC was evaluated calculating the time needed by saccharine crystals to reach the rhynopharynx, as this method has been demonstrated to be as reliable as the radioisotopic one [44]. It has been suggested, in a recent paper [40], to add charcoal powder to 3% saccharine, in order to increase information about the real mucociliary transport time.…”
Section: Methodsmentioning
confidence: 99%